Stosunek caratu do polskiej działalności dobroczynnej w Wilnie w I połowie XIX wieku - Korybut-Marciniak, Maria (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
The attitude of the tsarist regime against the Polish charitable initiatives in Vilnius was dependent on the political situation. Has evolved with the full approval of the time of Alexander I of suspicion and resentment for the reactionary governments of Nicholas I. Alexander I supported the initiative to establish the Vilnius Charitable Society. Nicholas I in every Polish initiative saw the source of unrest. The more that philanthropy is often combined with educational and patriotic activities. It should be emphasized that the charity, which in the first half of the nineteenth century, has become a social requirement, act as a binder different backgrounds. The best example of this is the Vilnius Charitable Society. This corresponded to the political line of Alexander I, but it has become dangerous for Nicholas. Tsar Nicholas I took control of all philanthropic initiatives in the lands of the Lithuanian – Belarusian.